Peran Good Corporate Governance (GCG) Sebagai Faktor Pemoderasi Pengaruh Manajemen Asset dan Struktur Modal Terhadap Kinerja Keuangan - Feni Nola, Ekta Rossivea; Setyahuni, Suhita Whini; Zaretta, Bara; Subagyo, Herry (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The aim of this research is to determine the impact of asset management and capital structure on financial performance, moderated by good corporate governance, in food and beverage issuers verified on the Indonesia Stock Exchange from 2019 to 2023. The research population is 90 companies, with sample selection carried out purposively. sampling, then 25 samples were obtained according to the criteria. The analysis assistance method used is panel data regression analysis with Eviews version 12.0. The findings of this research reveal that asset management and capital structure have a positive and significant effect on financial performance. Good Corporate Governance can moderate the influence of asset management on financial performance positively and significantly, but cannot moderate the influence of capital structure on financial performance positively and significantly.